BRINGING CULTURE TO LIFE: UTILIZING WOOD CARVING IN SPEAKING CLASS - Yektiningtyas, Wigati; Suhirman, Lalu; Ferdinandus, Adelce; Br Ginting, Juwita Purnamasari (LLT Journal: A Journal on Language and Language Teaching, 2024)
Sentani tribe in Papua had diverse cultural heritages that have now been neglected. One of them is wood carving. Despite its aesthetic and socio-cultural values, wood carving (ohomo) has not been acknowledged by most of the young Sentani generation. Thus, preservation is needed so that wood carving can be acknowledged, appreciated, and disseminated. One way of preserving this unique wisdom is by using it as a medium for teaching the English language. This will also help the learning process to be more contextual and challenging. By focusing on learning to speak, the objective of this study is to explore the strategies for teaching speaking using wood carving. This descriptive-qualitative study was conducted in Jayapura Regency Papua between May and July 2022. Data on wood carvings were collected between May and July 2022 from several informants, namely tribal chiefs, wood carvers, Sentani elders, and parents in East Sentani (Waena and Asei Island) and Central Sentani (Hobong and Yoboi). Teaching materials of wood carvings were tried out to 20 students of Senior High School Grade X from 4 different schools in Jayapura Regency via formal class and field trip. By infusing wood carving in learning to speak, the study found two important things, namely (1) the students were enthusiastic and motivated in speaking, and their confidence, as well as self-esteem, were improved; (2) the students appreciated wood carving as their cultural heritage and proud of their identity. Teachers’ creativity in infusing culture and their commitment to teaching played a significant role in reinforcing students’ appreciation of their culture and improvement in their speaking ability.